Principles of Self-Regulation in EFL mediated by Dialogic Tutoring Sessions - Imelda Zorro Rojas (Asociación Colombiana de Profesores de Ingles, 2019)
Students' engagement and determination require the use of self-regulated learning strategies to facilitate adequate preparation. This article reports a research study that looks into how eight instructors, who were trained to promote self-regulation, interact with 18 students of a Bachelor of Arts program in English language teaching in Bogotá. The problem was the prevalence of an instructional model of reproduction of knowledge in the English language classes taken by the 18 students. The pedagogical intervention introduces dialogic tutoring. The instructors' voices, in the role of tutors, and the students' voices, as tutees, were collected in 40 videos, a questionnaire, and a focus group. Grounded theory allowed transposing the identification of patterns, code tagging, and code grouping into concepts. This process generated four principles that worked positively in the promotion of self-regulation in this socially and culturally diverse sample of instructors and students, namely: (1) addressing needs, interests and beliefs; (2) setting goals; (3) scaffolding learning; (4) providing quality feedback.